Effect of synthetic cytokinin precusors on growth and yield of rice under limited water - Wan Mohd Zulkarnain,; Ismail, Mohd Razi; Mohd Saud, Halimi; Othman, Radziah; Habib, Sheikh Hasna; Kausar, Hossain (WFL Publisher, 2013)
Study was conducted at rain shelter house of Universiti Putra Malaysia to evaluate the effect of synthetic cytokinin application on the growth and yield of Malaysian rice (Oryza sativa L.) variety MR220 which was selected on the basis of its drought tolerant potential from a varietal screening trial. The experiment was conducted in a Complete Randomized Design (CRD) with 4 replications consisting of three treatments as flooded condition, cytokinin in saturated field condition and saturated field condition. The significant differences were observed for all the studied characters among the treatments. Application of cytokinin in saturated field condition helps rice plant to improve stomatal conductance, increase number of tillers and panicles per plant and eventually grain yield indicating the most suitable method for rice cultivation under limited water condition.